Anatomical Anterior Cruciate Ligament Reconstruction with Hamstring Tendon Autografts: A Comparative Study of Three Different Techniques - Wen, Zhenxing; Zhang, Hua; Yan, Wenlong; Mohamed, Sheikh Ibrahimrashid; Zhao, Pei; Huang, Xiao; Xu, Zijie; Zhang, Jian; Zhou, Aiguo (The Journal of Knee Surgery, 2020)
The ideal procedure for anterior cruciate ligament (ACL) reconstruction is one that can achieve anatomical restoration for a better ACL function. This retrospective comparative study was conducted to evaluate the objective and subjective clinical results of the conventional single-bundle femoral round (SBR) tunnel technique, the single-bundle femoral oval (SBO) tunnel technique, and the double-bundle (DB) surgical technique for anatomical ACL reconstruction with hamstring tendon autografts. Patients who underwent the SBO, SBR, and DB ACL reconstructions from January 2016 to August 2017 were included in this study. A total of 163 patients underwent different surgical techniques; 41 patients underwent the SBO procedure, 78 patients received SBR, and the remaining 44 patients underwent the DB procedure. The Lachman's test, pivot-shift test, Lysholm's score, International Knee Documentation Committee (IKDC) score, and Tegner's score were compared among groups postoperatively. KT-1000 was used to measure the anterior laxity of the knee. Magnetic resonance imaging was used to compare the ACL graft maturity. Second-look arthroscopy was conducted to compare the graft status and synovial coverage. Significant differences among groups were found with respect to the Lysholm's score, Tegner's score, and IKDC score. Patients in the SBO and DB groups acquired higher functional scores than the SBR group. More patients with positive pivot-shift test were observed in the SBR group than other groups at 12- and 24-month postoperative follow-ups. The postoperative KT-1000 was better in the SBO and DB groups than in the SBR group. The mean signal/noise quotient (SNQ) of the SBO group was 2.70 ± 0.92, significantly lower than 3.58 ± 1.21 of the SBR group. Despite a higher proportion of patients with grade B or C synovial coverage and partial graft injury found in the SBR group, there were no significant differences among the groups. The SBO and DB technique achieved better clinical results than the SBR technique. The SBO technique was indeed an ideal surgical procedure for ACL reconstruction provided that the shortcoming of DB technique must be taken into account. This is a Level III, retrospective comparative study.
Keywords: anterior cruciate ligament reconstruction; single bundle; double bundle; oval tunnel; hamstring tendon autografts